2001
DOI: 10.1111/j.1096-3642.2001.tb02239.x
|View full text |Cite
|
Sign up to set email alerts
|

The female abdomen of the viviparous earwig Hemimerus vosseleri (Insecta: Dermaptera: Hemimeridae), with a discussion of the postgenital abdomen of Insecta

Abstract: I'he viviparous, epizoic African earwigs of the genus Hemimerus are currently regarded as the sister taxon of the remaining Dermaptera (Forficulina). Exoskeleton, musculature, and part of the nervous system of the female abdomen, from segment IV on, are described. The morphological interpretation and homology relations of most components are discussed, using previous and original data on Forficulina, Zygentoma, Ephemeroptera, Orthoptera and Dictyoptera as a comparative framework. In the mid-abdominal segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…However, most of the issues could be resolved in the coming years by comparative work at the insect level (e.g., Klass 2001, 2003, 2008; Klass and Matushkina 2012; Klass et al 2012) – although some elements have remained problematic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the issues could be resolved in the coming years by comparative work at the insect level (e.g., Klass 2001, 2003, 2008; Klass and Matushkina 2012; Klass et al 2012) – although some elements have remained problematic.…”
Section: Resultsmentioning
confidence: 99%
“…It is a median part of the fragmented and reduced tergite 11 (see Klass 2001 for a discussion at the insect level). The mediotergite 11 is placed upon a small lobe, the dorsal fold 11 ( df11 , the ‘supraanal lobe’), which is a median remainder of a formerly wider fold df11 .…”
Section: Resultsmentioning
confidence: 99%
“…), eyes are entirely absent (e.g., Nakata and Maa 1974). Morphological and molecular phylogenetic studies showed that both Hemimeridae and Arixeniidae are specialized in-groups of the superfamily Forficuloidea that also includes free-living earwigs of the families Spongiphoridae, Chelisochidae, and Forficulidae (Klass 2001; Haas and Klass 2003; Jarvis et al 2005; Tworzydlo et al 2013; Kocarek et al 2013; Naegle et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The Dermaptera had been traditionally divided into three suborders, the Hemimerina, Arixeniina, and Forficulina [see 5]–[9], and all three suborders were treated as monophyletic [3], [5], [10], [11]. But studies published during the last decades indicated that the Hemimeridae and Arixeniidae are highly specialized lineages within the traditional Forficulina [12]–[18].…”
Section: Introductionmentioning
confidence: 99%
“…However, these characters may be plesiomorphic, and the unique hemimerid and arixeniid characters may be independently derived as a result of an epizoic lifestyle. Alternatively, one might suspect that many of the features that make epizoic groups seem more primitive than Forficulina could be due to secondary reduction [12].…”
Section: Introductionmentioning
confidence: 99%